Computational modelling study on phase stability of Li2MnO3 cathode material for lithium-ion batteries - Mphahlele, Mamonamane Gratitude (My University, 2023)
Li2MnO3 has been identified as a promising cathode material for secondary lithium-ion batteries due to its high theoretical capacity, nontoxicity and low cost. However, its application is hindered by structural transformations that lead to poor cycle capabilities. Cationic dopants have been used to reduce the collapse of the structure and they tend to improve the performance of cathode materials. As such, it is highly desirable to identify new doped structures as a remedial technique to optimize the properties of Li2MnO3. Firstly, the structural, electronic and mechanical properties of pristine Li2MnO3 were investigated. All calculations were carried out using VASP and PHONON codes as implemented in MedeA software, employing the density functional theory with Hubbard correction (DFT+U). The equilibrium lattice parameters were obtained by performing full structure optimization of Li2MnO3 and the results agreed well with those reported experimentally and in literature. The predicted heat of formation was negative indicating that the structure is thermodynamically stable. Furthermore, phonon dispersion curves showed no negative vibrations suggesting dynamic stability. The elastic constants revealed that the Li2MnO3 structure is mechanically stable. Secondly, the cluster expansion formalism was used for the generation of Li2Mn1-xNixO3, Li2Mn1-xCoxO3, Li2Mn1-xCrxO3 and Li2Mn1-xRuxO3 new phases with different concentrations and symmetries. The binary phase diagram predicted Li2Mn0.83Ni0.17O3, Li2Mn0.5Co0.5O3, Li2Mn0.5Cr0.5O3 and Li2Mn0.5Ru0.5O3 as the most stable phases of doped Li2MnO3. Lastly, Monte Carlo simulations were used to identify the ordered to disordered transition temperatures. Monte Carlo simulations produced thermodynamic properties for Li2Mn1-xNixO3, Li2Mn1-xCoxO3, Li2Mn1-xCrxO3 and Li2Mn1-xRuxO3 systems for the entire range of transition metals concentrations obtained from cluster expansion and it demonstrated that Li2Mn1-xNixO3, Li2Mn1-xCoxO3, Li2Mn1-xCrxO3 and Li2Mn1-xRuxO3 systems are phase separating systems at 0 K but changes to mixed systems at approximately 700 K-1700 K range which was confirmed by constructing the phase diagrams of all the four mixed systems. This validation will provide valuable insights which will guide experiments on where phase separation and mixed phases tend to occur in Li2Mn1-xNixO3, Li2Mn1-xCoxO3, Li2Mn1-xCrxO3 and Li2Mn1-xRuxO3 systems. The findings show the usefulness of combing CE and MC simulations when searching for new stable multi-component materials. The structures generated in this study may be useful in future as electrode materials in lithium-ion materials
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2023
Keywords: Li2MnO3; Lithium-ion batteries; Cathode materials; Lithium manganite; Lithium ion batteries; Cathode rays; Cathodes; Lithium compounds